Predator-prey Model with Monod-Haldane Functional Response and Fear Effect on Prey Dynamics - Wulandari, Nadila Agustin Eka; Dian Savitri (Jurnal Sains Dasar, 2025)
This study investigates a predator–prey model incorporating the Monod–Haldane functional response and the fear effect on prey. The objective of this research is to analyze population dynamics and system stability under the influence of prey fear. The model is examined through equilibrium and stability analysis and verified using numerical simulations with phase portraits. The results demonstrate that the fear effect significantly alters the stability of the interior equilibrium point and affects predator–prey population dynamics. These findings highlight the important role of behavioral factors in shaping ecological interactions.